Differential effects of dry vs. Wet heating of β-lactoglobulin on formation of sRAGE binding ligands and sIgE epitope recognition - Zenker, Hannah E.; Ewaz, Arifa; Deng, Ying; Savelkoul, Huub F.J.; Van Neerven, R. J.Joost; De Jong, Nicolettew; Wichers, Harry J.; Hettinga, Kasper A.; Teodorowicz, Malgorzata (Nutrients, 2019)
The effect of glycation and aggregation of thermally processed β-lactoglobulin (BLG) on binding to sRAGE and specific immunoglobulin E (sIgE) from cow milk allergic (CMA) patients were investigated. BLG was heated under dry conditions (water activity < 0.7) and wet conditions (in phosphate buffer at pH 7.4) at low temperature (<73ºC) and high temperatures (>90 ºC) in the presence or absence of the milk sugar lactose. Nε-(carboxymethyl)-l-lysine (CML) western blot and glycation staining were used to directly identify glycation structures on the protein fractions on SDS-PAGE. Western blot was used to specify sRAGE and sIgE binding fractions. sRAGE binding was highest under wet-heated BLG independent of the presence of the milk sugar lactose. Under wet heating, high-molecular-weight aggregates were most potent and did not require the presence of CML to generate sRAGE binding ligands. In the dry system, sRAGE binding was observed only in the presence of lactose. sIgE binding affinity showed large individual differences and revealed four binding profiles. Dependent on the individual, sIgE binding decreased or increased by wet heating independent of the presence of lactose. Dry heating required the presence of lactose to show increased binding to aggregates in most individuals. This study highlights an important role of heating condition-dependent protein aggregation and glycation in changing the immunogenicity and antigenicity of cow’s milk BLG.
Created from Fastlane, Scopus look-up
Keywords: Aggregation; Allergenicity; CML; Glycation; IgE binding; SRAGE; β-lactoglobulin